THE ROLE OF COMMUNITIES IN STRENGTHENING THE STARTUP ECOSYSTEM AND ENCOURAGING ENTREPRENEURIAL GROWTH IN THE DIGITAL ECONOMY ERA: Peran Komunitas dalam Memperkuat Ekosistem Startup dan Mendorong Pertumbuhan Kewirausahaan di Era Ekonomi Digital - Muhammad Riza Aziziy; Haniful Umam; Moh. Abdul Aziz (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Despite the growing importance of startup communities in the digital economy, existing studies largely emphasize structural and policy-driven factors while underexploring the community-based mechanisms that sustain entrepreneurial growth. Addressing this gap, this study examines how startup communities strengthen the digital startup ecosystem and contribute to entrepreneurial development in Indonesia. Using a qualitative exploratory case study approach, data were collected through in-depth interviews, participant observation, and document analysis across multiple startup communities. The findings demonstrate that communities actively enhance founders’ knowledge and capabilities through structured knowledge sharing, mentoring, and skill-development programs, while simultaneously expanding social capital and network access to funding and strategic partners. Moreover, community-based incubation and collaborative support accelerate innovation and product development. This study offers novelty by conceptualizing startup communities as relational and catalytic actors that integrate key ecosystem stakeholders, including government, investors, universities, and startups. Theoretically, it advances ecosystem and entrepreneurship literature by proposing a relational framework that explains community-driven value creation within digital startup ecosystems. Practically, the findings provide actionable insights for policymakers and ecosystem managers to design community-centered strategies that improve startup sustainability and foster inclusive digital entrepreneurial growth.